LAW ENFORCEMENT AGAINST ILLEGAL MINERS - Thamrin, Husni; Nursanthy, Aji Titin Roswitha; Thamrin, Muhammad Arganata (Awang Long Law Review, 2025)
Illegal mining refers to extraction or excavation activities carried out by individuals or companies without proper permits and without adhering to Good Mining Practices. Illegal mining is often conducted by communities using simple equipment, without licenses, and without environmental and safety considerations. It also involves financiers and traders. In certain cases, illegal mining is also carried out by companies. In this paper, the author uses a normative juridical approach. Due to this approach, this type of legal research is called normative legal research. Legal provisions, specifically Law No. 3 of 2020 concerning Amendments to Law No. 4 of 2009 on Mineral and Coal Mining, serve as primary legal sources. The author employs the library research method, which involves reviewing relevant books, magazines, journals, articles, and internet sources related to the discussed issue.